Optimizing Work Readiness Through Soft Skills, Motivation, and Internships - Nada, Nadyah Qotrrun; Ubaidillah, Hasan (Indonesian Journal of Islamic Studies, 2023)
Preparing students for the professional world is crucial, and this study evaluates how soft skills, motivation, and internship experiences influence their work readiness. Conducted among 202 Management students at Universitas Muhammadiyah Sidoarjo, Indonesia, the research reveals a significant positive correlation between soft skills development and work readiness, as well as the positive impact of motivation on students' preparedness for the job market. Internship experiences also play a vital role in enhancing students' understanding of real work environments. The findings emphasize the importance of integrating soft skills development into curricula, sustaining student motivation, and providing relevant internship opportunities to better equip students for professional challenges. Highlight: Soft skills development correlates positively with work readiness. Motivated students show greater preparedness for the job market. Internship experiences enhance students' understanding of real work environments. Keywoard: Work Readiness, Soft Skills, Motivation, Internship Experiences, Higher Education